EXPERIMENTAL PERFORMANCE ANALYSIS OF BIPLANE VAWT CONFIGURATIONS - Oulhaci, Z S; Imine, O; Ladjedel, O; Yahiaoui, T; Adjlout, L; Šikula, Ondřej (Journal of Applied Engineering Science, 2017)
This paper aim to develop a new Darrieus vertical axis wind turbine (VAWT) configurations based on the concept of biplane blades in order to improve the performances of the machine. The performances of the new design were investigated numerically and experimentally. Firstly a 2-D steady numerical simulation of an isolated two blades is carried out to exhibit the aerodynamic performance behavior. Secondly experiences are made on different Darrieus wind turbine by considering the biplane blade models. The experiments are carried out in wind tunnel by testing firstly: two, three and four blades Darrieus wind turbine as well as the biplane new configurations. The results of static torque and rotational speeds versus a wind velocity are presented. The obtained results corresponding to the new machines present a great improvement in the performances.
Keywords: CFD simulation; wind tunnel; biplane blades configuration; performance; Darrieus wind turbine